Optimal microgrid operation with electric vehicles - López Pérez, Miguel Ángel; Martín-Rivas, Sebastián; Aguado-Sánchez, José Antonio; De-la-Torre-Fazio, Sebastián Bienvenido (IEEE, 2012)
The concern about the complete depletion of fossil fuels along with the negative environmental impact of most of the current energy sources are significant reasons to think of a different way to produce electrical energy and, at the same time, satisfy the necessities for urban mobility. In this context, microgrids (MGs) are power networks which, among other properties, allow more flexible demand consumption, and also help with, the efficient integration of renewable resources and electric vehicles (EVs). However, the effect of the incorporation of EVs has to be taken into consideration with care, since that situation may drive to unfeasible operations in grids which have not been designed to support these particular elements. In this paper, a system composed of different agents is used to develop a market-oriented operation in a MG with several EV charge stations. It is expected that the system takes to an optimal management allowing a technically feasible operation considering the behaviour of every agent involved. The demand shifting and the flexible operation of EVs, spatial and temporal, are features that reduce costs and thus improve the benefit of the participants.
Artículo de 8 páginas (doble columna en inglés) desarrollado dentro del proyecto de investigación autonómico P08-TEP-4210 y del proyecto nacional ENE2011-27409, y presentado como ponencia oral en inglés en el congreso internacional con revisión por pares ISGT Europe 2011, celebrado en Manchester (UK), del 5 al 7 de diciembre de 2011. ISSN: 2165-4816, DOI: 10.1109/ISGTEurope.2011.6162696.
Keywords: Vehículos eléctricos; Electric vehicles; Renewable resources; Energy storage; Optimal power flow; Microgrids; Price responsive demand